Pengaruh Suction pada Pasien Post Op Craniectomy yang Terpasang Ventilator terhadap Saturasi Oksigen di ICU RSKD Dadi - Eka Amelia Trisusanti; Makkasau Plasay; Zukri Malik (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Head injury remains a leading cause of mortality, increasing intracranial pressure and requiring craniectomy. Postoperative patients on ventilators are at risk of respiratory distress due to secretion accumulation, which can lead to decreased oxygen saturation. This study aimed to determine the effect of suction on oxygen saturation in post-craniectomy patients on ventilators in the ICU of Dadi Regional General Hospital, South Sulawesi Province. This study used a quasi-experimental design with a one-group pretest-posttest approach. The sampling technique used purposive sampling. Oxygen saturation measurements were taken before and after suctioning and analyzed statistically. The results showed that the average oxygen saturation before suctioning was 94.14% and after suctioning increased to 99.81%. Most respondents experienced an increase in oxygen saturation after the intervention. The results of this statistical test indicate a significant effect between suctioning on increasing oxygen saturation (p = 0.000) with an effect size indicating a large impact. It is hoped that this action will be an effective intervention in increasing oxygen saturation in post-craniectomy patients who are on ventilators in the ICU.